2015
DOI: 10.1371/journal.pone.0124388
|View full text |Cite
|
Sign up to set email alerts
|

Language Differences in the Brain Network for Reading in Naturalistic Story Reading and Lexical Decision

Abstract: Differences in how writing systems represent language raise important questions about whether there could be a universal functional architecture for reading across languages. In order to study potential language differences in the neural networks that support reading skill, we collected fMRI data from readers of alphabetic (English) and morpho-syllabic (Chinese) writing systems during two reading tasks. In one, participants read short stories under conditions that approximate natural reading, and in the other,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 60 publications
(108 reference statements)
4
27
0
Order By: Relevance
“…These findings are consistent with studies directly contrasting single words and passages (Wang et al, 2015). This suggests that these regions support single-word processing specifically when compared to passage comprehension.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with studies directly contrasting single words and passages (Wang et al, 2015). This suggests that these regions support single-word processing specifically when compared to passage comprehension.…”
Section: Discussionsupporting
confidence: 91%
“…Participants completed a modified version of the story task described in Wang and colleagues (2015). In the scanner, participants passively read or listened to four stories by Hans Christian Andersen across four scan runs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reveals the relationship between visuospatial attention and Chinese reading fluency, to some extent. Moreover, Wang et al (2015) have found that silent reading of Chinese sentences would induce activation in the middle temporal gyrus which is thought to be important for the direct mapping of orthography to semantics. Based on this finding, it can be proposed that Chinese readers’ visual attention span may have an impact on the parallel processing of multiple orthographic units of Chinese characters which in turn may affect the efficiency of their sentence comprehension ability during the silent reading task.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this model, global processing typically requires a larger visual attention span than analytic processing (Bosse et al, 2007). Wang et al (2015) has showed that silent reading mainly relies on the global orthographic-to-semantic mapping. In contrast, oral reading fluency has been reported to be involved in the orthographic-to-phonological mapping.…”
Section: Discussionmentioning
confidence: 99%